2020
DOI: 10.3390/su12187573
|View full text |Cite
|
Sign up to set email alerts
|

Winter Irrigation Effects on Soil Moisture, Temperature and Salinity, and on Cotton Growth in Salinized Fields in Northern Xinjiang, China

Abstract: Winter irrigation affected the movement of soil moisture, temperature, and salt, which was an effective improvement measure widely used in seasonal freeze–thaw areas. In this paper, we investigated the effects of different salinized cotton fields (mild salinization (S1), 5.15 g·kg−1; moderate salinization (S2), 8.17 g·kg−1; severe salinization (S3), 11.15 g·kg−1) and different winter irrigation rates (W0, 0 m3·hm-2; W1, 3000 m3·hm-2; W2, 3600 m3·hm-2; W3, 4200 m3·hm-2) on soil moisture, temperature, salinity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…Also shown in this Table is a decrease in soil bulk density with saline water W2, W3, in second and third soil depths. These results fall in line with findings of (Li et al, 2020) who found the same trend. These results could be due to soil salinity which increase aggregates of particles and decrease soil bulk density (Bless et al, 2022).…”
Section: Effect Of Different Treatments On N P and K Uptakes In Tuber...supporting
confidence: 93%
“…Also shown in this Table is a decrease in soil bulk density with saline water W2, W3, in second and third soil depths. These results fall in line with findings of (Li et al, 2020) who found the same trend. These results could be due to soil salinity which increase aggregates of particles and decrease soil bulk density (Bless et al, 2022).…”
Section: Effect Of Different Treatments On N P and K Uptakes In Tuber...supporting
confidence: 93%
“…Therefore, winter irrigation is a widely effective measure to treat soil salinization. The optimal irrigation amount for winter irrigation in northern Xinjiang is still guided by experience rather than by research, and the leaching would occur [44]. This phenomenon also exists in southern Xinjiang.…”
Section: Nitrogen Loss Patternsmentioning
confidence: 99%
“…Moisture is important for freezing resistance in alfalfa. Soil moisture has a buffering effect on the soil cooling rate because of its high heat capacity and thermal conductivity and this can mitigate the damage caused by drastic changes in temperature during winter (Li et al, 2020). When alfalfa overwinters, its degree of frost resistance might be affected by soil water deficit caused by seepage or evaporation.…”
Section: Role Of Osmotic Regulation and Cryoprotectant Substances In ...mentioning
confidence: 99%
“…Because there are not sudden changes in temperature, cryogenic stress is relatively light. This buffering effect can mitigate damage from sudden large changes in air temperature, thereby improving the overwintering survival rate (Sun et al, 2004;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%